1997
DOI: 10.1104/pp.115.4.1609
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Xanthophyll-Cycle Activity in Different Antenna Subcomplexes in the Photosynthetic Membranes of Higher Plants (The Relationship between Zeaxanthin Conversion and Nonphotochemical Fluorescence Quenching)

Abstract: The generation of nonphotochemical quenching of chlorophyll fluorescence (qN) in the antenna of photosystem II (PSII) is accompanied by the de-epoxidation of violaxanthin to antheraxanthin and zeaxanthin. The function of zeaxanthin in two mechanisms of qN, energy-dependent quenching (qE) and photoinhibitory quenching (qI), was investigated by measuring the de-epoxidation state in the antenna subcomplexes of PSII during the generation and relaxation of qN under varying conditions. Three different antenna subcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(154 citation statements)
references
References 33 publications
8
144
1
1
Order By: Relevance
“…The pigment composition of isolated samples was determined by reversephase HPLC according to the method of Faber et al (41). Standard absorption spectra were measured using an SLM DW2000 spectrophotometer as described previously (35).…”
Section: Methodsmentioning
confidence: 99%
“…The pigment composition of isolated samples was determined by reversephase HPLC according to the method of Faber et al (41). Standard absorption spectra were measured using an SLM DW2000 spectrophotometer as described previously (35).…”
Section: Methodsmentioning
confidence: 99%
“…Because the adaxial side of the leaf is that which is exposed to the highest light intensity, it is not immediate to reconcile the expression pattern of Lhcb7 in the leaf with the protein's predicted light-harvesting function in light-limiting conditions. Alternatively, Lhcb7 could function in nonphotochemical quenching to dissipate energy under conditions where the absorbed light exceeds the electron transfer capacities of the thylakoid complexes contributing to primary photochemistry (Szabo et al, 2005), and a similar function has indeed already been suggested for Lhcb4, Lhcb5, and Lhcb6 (Farber et al, 1997;Dall'Osto et al, 2005). Carbon dioxide fixation is proportional to light intensity, but Rubisco content and carbon fixation at the abaxial and adaxial surfaces of the leaf are comparable (Nishio et al, 1993;Sun and Nishio, 2001).…”
Section: Uniqueness and Redundancy Among Rbcs And Lhc Expression Pattmentioning
confidence: 99%
“…Previous work with spinach (Spinacia oleracea) involved IEF analysis of wild-type thylakoids treated to accumulate zeaxanthin (Ruban et al, 1994;Fä rber et al, 1997), and yet no report of a pI-shifted CP26 was made. We think this is probably due to the use of different procedures: in earlier work, direct IEF of detergent solubilized membranes was applied, whereas this work includes enrichment of the sample before IEF by sucrose gradient ultracentrifugation.…”
Section: Is Ph-independent Quenching Restricted To Cp26?mentioning
confidence: 99%